2014
DOI: 10.1039/c4cp03398a
|View full text |Cite
|
Sign up to set email alerts
|

A study of the ice–water interface using the TIP4P/2005 water model

Abstract: In this work we study the ice-water interface under coexistence conditions by means of molecular simulations using the TIP4P/2005 water model. Following the methodology proposed by Hoyt and co-workers [J. J. Hoyt, M. Asta and A. Karma, Phys. Rev. Lett., 86, 5530, (2001)] we measure the interfacial free energy of ice with liquid water by analysing the spectrum of capillary fluctuations of the interface. We get an orientationally averaged interfacial free energy of 27(2) mN/m, in good agreement with a recent est… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 49 publications
6
49
0
7
Order By: Relevance
“…The error bars are calculated taking into consideration the uncertainties on the estimated melting temperature (∼10 K) and the fitting procedure. As compared to previous studies on molecular compounds using the capillary fluctuation method, 48,112 the linear domain is more limited and the data are much noisier. It might indicate that some interfaces are not completely rough or a possible size effect.…”
Section: Simulation Detailsmentioning
confidence: 91%
“…The error bars are calculated taking into consideration the uncertainties on the estimated melting temperature (∼10 K) and the fitting procedure. As compared to previous studies on molecular compounds using the capillary fluctuation method, 48,112 the linear domain is more limited and the data are much noisier. It might indicate that some interfaces are not completely rough or a possible size effect.…”
Section: Simulation Detailsmentioning
confidence: 91%
“…It is not obvious that we should compare these values for stacking-disordered ice to literature values of interfacial energy of hexagonal ice, but computational studies suggest there is only a small difference in interfacial energy between the different forms of ice I, 78,79 and that the basal face of hexagonal ice at equilibrium may be stacking disordered. 80 Hence, we cautiously compare our values of σ sd,l at the melting temperature with values determined for hexagonal ice also at the melting temperature. From experiments, there is a substantial spread of the reported interfacial energy at 273.15 K, 1 but it has been suggested that the value of Hardy 81 of 29.1 ± 0.8 mJ m −2 may be the most reliable.…”
Section: Fitting the Cnt-based Model To Experimental Datamentioning
confidence: 99%
“…1). Comparing our results for the ice-vapor interface with our previous study of the ice-water interface will prove insightful [44]. Since we aim at studying large wavelength fluctuations, we prepare the exposed faces with an elongated geometry, with box side L x ≫ L y .…”
mentioning
confidence: 99%